App-based multimodal lifestyle-intervention for essential hypertension (HYPE): a decentralized randomised controlled trial - Beger, Christian; Lehmann, Marco; Kaup, Marisa; Jones, Lucy; Mijuskovic, Ana; Limbourg, Florian P. (Frontiers in Digital Health, 2025)
BackgroundLife-style interventions are effective in lowering blood pressure (BP) and reducing cardiovascular risk, but implementation is poor. We aimed to evaluate the efficacy of an app-based multimodal lifestyle intervention in reducing BP in patients with uncontrolled hypertension.MethodsIn a decentralized, single-blinded, randomized-controlled trial, adults with uncontrolled hypertension by home BP measurement were randomized to 12 weeks of app-based multimodal lifestyle intervention or care as usual. The primary outcome was the difference of mean systolic BP after 12 weeks. Secondary outcomes were mean diastolic BP difference, and changes in body weight, health-related quality of life, and food literacy. An intention-to-treat analysis with multiple imputation by chained equations (MICE) was performed.ResultsFrom June 13, 2024, to September 30, 2024, a total of 139 pts. were randomized with a mean baseline BP of 142/88 mmHg, of which 55% were females. After 12 weeks, there was a significantly lower systolic BP in the intervention group (−8.5 mmHg, [95% CI: −11.0 to −5.9], p < 0.001). At this time point, the intervention group also showed significantly lower diastolic BP (−5.06 mmHg), a larger relative reduction in body weight (−2.88%) as well as larger improvements in health-related quality of life and food literacy. Responder analysis confirmed that the effects were large and consistent across outcomes. No serious adverse events related to the intervention occurred during the trial.ConclusionA digital multimodal lifestyle intervention may clinically improve general hypertension care and should be evaluated in larger trials.Clinical Trial Registration: https://drks.de/search/de/trial/DRKS00034348, identifier (DRKS00034348).